THE EFFECT OF FEEDING DRAGON FRUIT PEEL EXTRACT (Hylocereus polyrhizus) IN DRINKING WATER ON THE CARCASS AND CARCASS PARTS OF THE KUB CHICKEN - E. E., Tampubolon; Dewi, G. A. M. K.; Puspani, E. (Jurnal Peternakan Tropika, 2024)
KUB chicken productivity is still low and it is necessary to increase productivity, one of which can be done through the addition of natural feed additives in drinking water.  This study aims to determine the effect of giving dragon fruit peel extract through drinking water on carcasses and carcass parts of KUB chickens, the research was conducted in April-June 2023.  The research design used was RAL consisting of 4 treatments and 4 replicates.  Each replicate consisted of 5 KUB chickens, so there were 80 KUB chickens.  The four treatments were: drinking water without dragon fruit peel extract as control (P0), drinking water with dragon fruit peel extract as much as 3% (P1), 6% (P2) and 9% (P3).  The observed variables: slaughter weight, carcass weight, carcass percentage and percentage of carcass parts (breast, wings, back, upper thigh and lower thigh).  The results showed that giving 6% dragon fruit peel extract through drinking water can significantly (P<0.05) increase the percentage of carcass, and giving 9% dragon fruit peel extract through drinking water can significantly (P<0.05) increase the slaughter weight, carcass weight, and the percentage of chest, upper thigh and lower thigh and significantly (P<0.05) affect the percentage of the back, but give results that are not significantly different (P>0.05) on the percentage of carcass parts of the wings.   Based on the results of the study, it can be concluded that the provision of dragon fruit peel extract through drinking water with a level of 6% is able to increase the percentage of carcasses and a level of 9% is able to increase slaughter weight, carcass weight, percentage of breast, upper thigh, lower thigh and affect the percentage of the back of 9-week-old KUB chickens.